Exploring task-service fit and usefulness on branded applications continuance. Issue 6 (11th September 2017) - Fang, Yu-Hui
Abstract : Purpose: Providing that branded applications (apps) became a new trend in mobile marketing, the purpose of this study, thus, is to explore how to promote app users' continuance intention and purchase intention (i.e. "app continuance") toward a specific branded app. Design/methodology/approach: By integrating both goods-dominant logic (GDL) and service-dominant logic (SDL), this study uses a unifying model to examine whether perceived usefulness and task-service fit (TSF) have different effects on the two parts of app continuance. This study identifies task characteristic and four service characteristics (interactivity, presence, localization and ubiquity) as antecedents of TSF. Furthermore, psychological barriers are examined as mediators of TSF and purchase intention within SDL. Data collected from 631 users of the targeted branded apps support all of the proposed hypotheses. Findings: The findings show that besides perceived usefulness, TSF is an essential determinant of both app continuance in the context of branded apps and a partial mediator of psychological barriers between TSF and purchase intention. Originality/value: Unlike prior studies, which have focused on traditional GDL to examine continuance intention, this study incorporates SDL and the notion of psychological barriers to explore such matters. The evidence concerning the significantly higher explanatory power of the full model suggests that a deeper understanding of the antecedents of app continuance is possible when the alternative view is taken into consideration, thus providing a promising avenue for future research.